Pengaruh Komitmen Organisasi Terhadap Kinerja Pegawai Di Badan Kepegawaian Dan Diklat Daerah Kabupaten Enrekang (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
this study aimed to determine the effect of organizational commitment on employee performance in the Enrekang District Personal and Training Agency. This research used quantitative methods. The population in this study were 40 employees at the Enrekang Regency Employee and Education Agency Office. This study used saturated sampling in which all members of the population used as samples. Data collecting used instruments such as questionnaires and observations. The data were analyzed using descriptive statistical analysis and simple linear regression analysis with SPSS. The results showed that the influence of organizational commitment employee performance in the Enrekang District Personnel and Training Agency was very significant. Therefore the hypothesis in the study was accepted because it was supported by the significance value. So in other words the independent variable  of organizational commitment was able to explain the magnitude of the dependent variable of employee performance, employee performance could be seen in table 4.61 which showed that employee performance was in the good caregory of 78.6% result obtained from the average questionnaire researchers.